2012
DOI: 10.1111/j.1471-0528.2012.03321.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and folate concentrations in early pregnancy and the risk of adverse pregnancy outcomes: the Generation R Study

Abstract: Objective To investigate associations between early pregnancy homocysteine, folate and vitamin B12 concentrations and placental weight, birthweight and adverse pregnancy outcomes.Design Population-based birth cohort study.Setting Rotterdam, the Netherlands.Population Cohort of 5805 pregnant women.Methods To analyse homocysteine, folate and vitamin B12 concentrations, blood was drawn in early pregnancy. These concentrations were divided into quintiles. Information on birth outcomes was retrieved from medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
165
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(195 citation statements)
references
References 53 publications
(68 reference statements)
16
165
0
6
Order By: Relevance
“…Takimoto et al (2011) reported a significant increase in birth weight (b = 0.08; 95 % CI 0.01, 0.15) associated with dietary intake of vitamin B 12 during the third trimester of pregnancy, while Sukla et al (2013) observed that women with deficient plasma vitamin B 12 were two times more likely of having a low weight infant than those without this deficiency. Other authors did not find an association between vitamin B 12 and birth weight (Relton et al 2005, Bergen et al 2012.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Takimoto et al (2011) reported a significant increase in birth weight (b = 0.08; 95 % CI 0.01, 0.15) associated with dietary intake of vitamin B 12 during the third trimester of pregnancy, while Sukla et al (2013) observed that women with deficient plasma vitamin B 12 were two times more likely of having a low weight infant than those without this deficiency. Other authors did not find an association between vitamin B 12 and birth weight (Relton et al 2005, Bergen et al 2012.…”
Section: Discussionmentioning
confidence: 85%
“…Pregnant women carriers of 677C[T polymorphism in MTHFR gene have an enzymatic variant with less activity and, therefore, less 5-methyltetrahydrofolate availability. In these women, a deficient dietary intake of vitamin B 12 can produce an increase of maternal serum Hcy levels, which during pregnancy have been related with alterations in the vascular endothelium at the placental level, leading to adverse reproductive effects such as preeclampsia, miscarriage and restricted fetal growth (Bergen et al 2012). Another potential mechanism is that vitamin B 12 deficiency reduces the methionine metabolism and can affect the patterns of epigenetic modifications such as DNA methylation that alter the gene expression and thus affect the fetal development (Rush et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that, in addition to deficiencies of vitamins B-12 and folate alone, unbalanced vitamin B-12 and folate intake or status may interact and increase risk of adverse pregnancy outcomes (100, 101). Higher tHcy concentrations were associated with significantly increased risk of LBW in a study in Netherlands (89). Similarly, in a study in Japan, maternal tHcy concentrations were associated with significantly lower birth weight: each 0.1-mmol/L increase in maternal tHcy concentrations during the third trimester was associated with a 151-g lower infant birth weight (P < 0.01) (102).…”
Section: Literature Reviewmentioning
confidence: 88%
“…A number of studies have reported an association of vitamin B12 deficiency with infertility, IUGR, preeclampsia and early pregnancy loss [58][59][60][61][62][63]. One study in Chinese women found that inadequate preconception vitamin B12 (<258 pmol/L) was associated with a 60% increased risk of preterm delivery [64].…”
Section: Adverse Pregnancy Outcomesmentioning
confidence: 99%